Undiagnosed maternal diaphragmatic hernia – a management dilemma - Maya Reddy; Annie Kroushev; Kirsten Palmer (BMC Pregnancy and Childbirth, 2018)
Abstract Background Maternal diaphragmatic hernias identified during pregnancy are rare and pose significant management challenges with regards to timing and mode of both delivery and hernia repair. Case presentation We describe a case of a maternal diaphragmatic hernia diagnosed at 31 weeks gestation in the setting of acute upper abdominal pain. Due to no evidence of visceral compromise and a stable maternal condition, the patient was conservatively managed, allowing for further foetal maturation. Delivery by caesarean section occurred following concerns of malnutrition and partial bowel obstruction. This was followed by immediate surgical repair of the hernia. The patient had an uncomplicated recovery. Conclusion Maternal diaphragmatic hernias in pregnancy require multidisciplinary care and individualised management in order to allow for the optimal outcome for mother and foetus.